A case of adrenal Cushing's syndrome with bilateral adrenal masses. (1st May 2016) - Guo, Ya-Wun; Hwu, Chii-Min; Won, Justin Ging-Shing; Chu, Chia-Huei; Lin, Liang-Yu
Summary: A functional lesion in corticotrophin (ACTH)-independent Cushing's syndrome is difficult to distinguish from lesions of bilateral adrenal masses. Methods for distinguishing these lesions include adrenal venous sampling and 131 I-6β-iodomethyl-19-norcholesterol ( 131 I-NP-59) scintigraphy. We present a case of a 29-year-old Han Chinese female patient with a history of hypercholesterolaemia and polycystic ovary syndrome. She presented with a 6month history of an 8kg body weight gain and gradual rounding of the face. Serial examinations revealed loss of circadian rhythm of cortisol, elevated urinary free-cortisol level and undetectable ACTH level (<5pg/mL). No suppression was observed in both the low- and high-dose dexamethasone suppression tests. Adrenal computed tomography revealed bilateral adrenal masses. Adrenal venous sampling was performed, and the right-to-left lateralisation ratio was 14.29. The finding from adrenal scintigraphy with NP-59 was consistent with right adrenal adenoma. The patient underwent laparoscopic right adrenalectomy, and the pathology report showed adrenocortical adenoma. Her postoperative cortisol level was 3.2μg/dL, and her Cushingoid appearance improved. In sum, both adrenal venous sampling and 131 I-NP-59 scintigraphy are good diagnostic methods for Cushing's syndrome presenting with bilateral adrenal masses. Learning points: The clinical presentation of Cushing' syndrome includes symptoms and signs of fat redistribution and protein-wasting features. The diagnosis of patients with ACTH-independent Cushing's syndrome with bilateral adrenal masses is challenging for localisation of the lesion. Both adrenal venous sampling and 131 I-NP-59 scintigraphy are good methods to use in these patients with Cushing's syndrome presenting with bilateral adrenal masses.